Trophic interactions affecting a key ecosystem component: a multi-stage analysis of the recruitment of the Barents Sea capelin - Hjermann, Dag Ø.; Bogstad, Bjarte; Dingsør, Gjert Endre; Gjøsæter, Harald; Ottersen, Geir; Eikeset, Anne Maria; Stenseth, Nils Christian (Canadian Journal of Fisheries and Aquatic Sciences, 2010)
The Barents Sea stock of capelin (Mallotus villosus) has suffered three major collapses (>90% reduction) since 1985 due to recruitment failures. As capelin is a key species in the area, these population collapses have had major ecosystem consequences. By analysing data on spawner biomass and three recruitment stages (larvae, 0-group, and 1-year-olds), we suggest that much of the recruitment failures are caused by predation from herring (Clupea harengus) and 0-group and adult Northeast Arctic cod (Gadus morhua). Recruitment is furthermore positively correlated with sea temperatures in winter and spring. Harvesting of maturing capelin on their way to the spawning grounds reduced the abundance of larvae significantly, but this reduction to a large extent is compensated for later in life, as mortality is strongly density-dependent between the larval stage and age 1. Altogether, our study indicates a very high importance of trophic interactions, consistent with similar findings in other high-latitude marine ecosystems.